2007
DOI: 10.3998/ark.5550190.0008.d07
|View full text |Cite
|
Sign up to set email alerts
|

A new and efficient protocol for preparation of thiol esters from carboxylic acids and thiols in the presence of 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium tetrafluoroborate (TBTU)

Abstract: A novel and convenient method has been developed for the synthesis of thiol esters from the corresponding carboxylic acids and thiols at room temperature using 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium tetrafluoroborate (TBTU) as the coupling reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In this study, APG-loaded PLGA-NPs were surface-functionalized with DMSA using an EDC/NHS coupling method to obtain the corresponding thiol ester. 50 During nanoparticle fabrication, TPGS was used as a stabilizer to improve emulsification and encapsulation efficiency. FTIR studies revealed the absence of any chemical interaction of the flavonoid and formulation ingredients during preparation.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, APG-loaded PLGA-NPs were surface-functionalized with DMSA using an EDC/NHS coupling method to obtain the corresponding thiol ester. 50 During nanoparticle fabrication, TPGS was used as a stabilizer to improve emulsification and encapsulation efficiency. FTIR studies revealed the absence of any chemical interaction of the flavonoid and formulation ingredients during preparation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As reported, an active lung targeting strategy of magnetic NPs could be improved through conjugation of DMSA on the surfaces of NPs. In this study, APG-loaded PLGA-NPs were surface-functionalized with DMSA using an EDC/NHS coupling method to obtain the corresponding thiol ester . During nanoparticle fabrication, TPGS was used as a stabilizer to improve emulsification and encapsulation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The dialyzed samples were lyophilized and stored in an auto-dry desiccator for future use. PPG-cRGD NPs were synthesized by esterification reaction as reported previously [ 28 , 29 ]. Briefly, PPG (50 mg) was added with 4-dimethylaminopyridine (DMAP) (100 mmol) and cRGD (60 mmol) in 10 mL of DMF.…”
Section: Methodsmentioning
confidence: 99%
“…92 [31] (1.0 mmol), olefin/alkyne/alkyl or acyl halide (1.0 mmol), Fe 3 O 4 MNPs (0.04 mmol, 4 mol%), neat, room temperature. b Isolated yield.…”
Section: CLmentioning
confidence: 99%
“…In a recent report, bis(triflimide)iron(III) salt was introduced as a potential catalyst for the hydrothiolation of styrene derivatives in a Markovnikov fashion [29]. The growing importance of thioethers and thiol esters in organic synthesis has stimulated recent extensive research towards improved methods for their preparations [26][27][28]30,31]. In continuation of our interest in applications of Fe 3 O 4 MNPs for organic transformations [11d-e], herein we report a simple and highly efficient protocol for the preparation of thioethers, vinyl thioethers, thiol esters and thia-Michael adducts under neat and neutral reaction conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%